Peningkatan Kualitas Citra Karikatur Menggunakan Filter Maksimum dan Filter Median - Noviani Noviani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Quality improvement is basically how to overcome various problems that will arise to achieve the expected quality. Quality improvement is an activity to measure performance, benchmarking with standards and any systematic effort to improve performance in order to achieve expected standards. In improving the quality of this caricature image using a maximum filter and a median filter is basically a method to reduce or eliminate noise in a digital image or image, smoothing with a median filter to replace pixels with the highest value of a series formed from a matrix that matches the size of filter window. This filter works by selecting the intensity of the pixel in the middle, after pixel_pixel included in the filter is sorted